The National Identity of the Jewish Community Living in the United States - Huszár Hedvig (2003)
In my work, I analyse the different components of the national identity of the Jewish community living in the US. My claim is that these components influence their behaviour toward the American society. My discussion is divided into four parts. At first I examine the origin of the Jews, including the time and the country from where the first refugees came. Also, here I point out the role of Israel and the importance of Zionism. Secondly, I analyse their behaviour towards the American Gentiles and point out their unusual everyday habits and their educational system. Thirdly, I argue that the Jews are a religious community rather than an ethnic group. I believe that because of their religion, which is the base of their lives, they must be considered as a religious group of people. Fourthly, I intended to examine the level of discrimination the Jews receive nowadays and they received in the past. I believe that they face less discrimination that any other minority groups, like the Blacks. One may discover that in most of the cases the Jews behave in a strange way, at least strange for the non-Jews, but it is related to the fact that they came from different backgrounds, face discriminations and reject common American practices.